Is relational continuity of care as important to people as policy makers think? Preferences for continuity of care in primary care. (19th March 2021) - Norwood, Patricia; Correia, Isabel; Heidenreich, Sebastian; Veiga, Paula; Watson, Verity
Abstract: Background: In 2005, the Portuguese government launched a Primary Care reform that aimed to reinforce continuity of care. After a promising start, the reform is still incomplete and continuity has been compromised by the lack of General Practice doctors. Objective: This study evaluates public preferences for relational continuity of care alongside other attributes of Primary Care services in Portugal. Methods: We use a discrete choice experiment (DCE) to evaluate preferences and estimate the population's willingness to pay (WTP) for Primary Care attributes. We use a sequential, mixed-methods approach to develop a D-efficient fractional factorial design for the DCE. Five attributes were included in the DCE and there were 32 DCE choice sets. The data collection was conducted in 2014 and the final sample had 517 respondents. A random parameters multinomial logit was used to analyse the data. Results: We find that respondents value relational continuity of care, but that the current focus of the Portuguese NHS on relational continuity at the expense of other attributes is too simplistic. Conclusions: Relational continuity should be part of a broader policy that emphasizes person-centred care and considers the preferences of patients for Primary Care attributes.